AN INVESTIGATION TO THE CAUSES OF MASS FAILURE IN EXTERNAL EXAMINATION - SANYOG KUMAR PREMI (International Journal of Multidisciplinary Research and Studies, 2020)
The dismal performance of secondary school pupils in certificate tests, with a particular emphasis on the English language, has been roundly criticized on an ongoing basis by a large number of concerned individuals as well as organizations. In point of fact, governments, educational groups, and parents express their concern on an annual basis over the declining performance of their children and grandchildren in these tests. Due to the significant role that the English language plays in the overall educational development of pupils, poor performance in the English language may be immensely irritating for many stakeholders. For example, admittance to higher education institutions is not feasible without a passing grade in English. Having a solid command of the language also makes it easier for students to understand the material covered in other classes. When it appears to everyone that governments at all levels are doing everything possible to improve the situation, the issue of poor performance in English becomes increasingly concerning. This is especially the case when it seems to everyone that governments at all levels are doing everything possible to improve the situation. Given that the English language is accorded a prominent position in the National Policy on Education, what are your thoughts on this matter? What are your thoughts on the increased amount of time on the school schedule designated for the instruction of the English language (as well as mathematics)? Because the majority of communication that takes place between kids in a school setting is carried out in English, that language is always being utilized. In spite of everyone's best efforts, the pattern of inadequate performance in English language classes has continued to deteriorate.